Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1002/rmv.2181
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of serological tests and kinetics of severe acute respiratory syndrome coronavirus 2 antibody: A systematic review and meta‐analysis

Abstract: This study aimed to assess the diagnostic test accuracy (DTA) of severe acute respiratory syndrome coronavirus 2 (SARS-COV-2) serological test methods and the kinetics of antibody positivity. Systematic review and meta-analysis were conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guideline. We included articles evaluating the diagnostic accuracy of serological tests and the kinetics of antibody positivity. MEDLINE through PubMed, Scopus, medRxiv and bioRxiv were sourc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
66
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(73 citation statements)
references
References 46 publications
4
66
0
1
Order By: Relevance
“…While molecular tests and rapid antigen tests are targeted for early diagnosis, serology tests play a different and perhaps even larger role by supporting epidemiological studies, furthering the understanding of longitudinal immunity, and in assessing the efficacy of vaccine development [5]. The efficient use of serology tests in understanding immunity, both in response to disease or vaccination, requires evaluation of any given assay's diagnostic performance and discriminative ability [6,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While molecular tests and rapid antigen tests are targeted for early diagnosis, serology tests play a different and perhaps even larger role by supporting epidemiological studies, furthering the understanding of longitudinal immunity, and in assessing the efficacy of vaccine development [5]. The efficient use of serology tests in understanding immunity, both in response to disease or vaccination, requires evaluation of any given assay's diagnostic performance and discriminative ability [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Coronavirus spikes form large heavily glycosylated homo-trimeric complexes, yet due to their instability in vitro, monomeric presentations of the spike protein, including the receptor binding domain (RBD) only, have been most prevalently used in immunoassays. While the diagnostic performance of assays using RBD as an antigen have shown better results compared to spike and nucleoprotein antigens [6], the trimeric form was shown to be associated with greater sensitivity for the detection of SARS-CoV-2 IgG antibody in human samples [9]. Here, the performance of the LIAISON ® SARS-CoV-2 TrimericS IgG assay (Emergency Use Authorization, EUA) was evaluated against two assays that utilize the spike RBD as capture antigen: the Siemens ADVIA Centaur COV2G assay in sample remainders from a routine laboratory workflow in New York experiencing high disease prevalence; the Beckman ACCESS SARS-CoV-2 IgG assay from a New Mexico laboratory confronted with a lower disease prevalence.…”
Section: Introductionmentioning
confidence: 99%
“…Elecsys-N is an assay for qualitative detection of total anti-SARS-CoV-2 antibodies against SARS-CoV-2 nucleoprotein (N). The manufacturer's extensive evaluation showed 99.80% specificity and 99.5% sensitivity, and manufacturer-independent evaluations even with values spanning manufacturer claims [ 3 , 5 , [18] , [19] , [20] , [21] , [22] , [23] , [24] ] (see Supplementary material, item S5 ).…”
Section: Methodsmentioning
confidence: 99%
“…Detecting severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) RNA in nasopharyngeal swabs is a COVID-19 reference diagnostic standard [ 1 , 2 ]. However, because of a significant number of asymptomatic/mild infections, demanding implementation and scale-up of molecular testing and frequent changes in testing strategies, the SARS-CoV-2 RNA positives identified represent only the tip of the pandemic iceberg [ [2] , [3] , [4] ]. As a result, seroprevalence surveys measuring the population immune response to SARS-CoV-2 remain integral for understanding cumulative population exposure and insight into pandemic dynamics during the COVID-19 pre-vaccination era [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…16 In short, the evaluation of SARS-CoV2 IgM and IgG antibodies serves epidemiological purposes for COVID-19 that are recognized. 17 Many conventional diagnostic studies have reported the diagnostic significance of antibody testing, [18][19][20] but in the general population antibody test should not be used as a diagnostic index. It has diagnostic significance only for suspected cases.…”
mentioning
confidence: 99%